Nightmares at the End of History: Francis Fukuyama's Encounters with Science Fiction. Issue 3 (1st December 2022) - Dyson, Stephen Benedict
Abstract : The public intellectual and political theorist Francis Fukuyama is best known for insisting that the end of the twentieth century saw the permanent triumph of the liberal capitalist state, a victory declared in his most famous work, The End of History and the Last Man (1992). Yet his writings and subsequent public interventions are burdened by dark thoughts about the future of this system of government, thoughts that are manifest in an engagement with dystopian science fictions such as Blade Runner (1982), Children of Men (2006), and Mad Max 2: The Road Warrior (1981). Fukuyama's engagement with these texts reveals that he holds deep misgivings about the very liberal capitalism he is commonly read as championing. That this celebrated neoliberal thinker is not at peace with the dominant ideology perhaps puts a dent in its armor and, just maybe, provides an opening for a progressive alternative.